Analysis of Imperative Speech Acts in Angga Dwimas Sasongko's Film Today We’ll Talk About That Day - Houtman; Arfiah; Surismiati (IJLHE: International Journal of Language, Humanities, and Education, 2024)
Imperative speech acts play a vital role in various aspects of communication, both in daily interactions and in media such as films. These speech acts serve essential functions in regulating, controlling, and directing the actions of others. This study aims to identify and describe the functions of imperative speech acts in the film Today We’ll Talk About That Day by Angga Dwimas Sasongko and to determine their relevance to learning Indonesian in high schools. The theoretical framework used in this study includes Searle's and Kunjana Rahardi's theories. The data source for the research is the film Today We’ll Talk About That Day, which was released in July 2023. A qualitative method was employed, with data collection techniques including observation, documentation, and interviews. The data analysis process involved four stages: data collection, data reduction, data presentation, and verification or conclusion. The results of the study revealed 42 instances of imperative speech acts in the film Today We’ll Talk About That Day. These were categorized into five functions: (1) requests, (2) orders, (3) invitations, (4) granting permission, and (5) prohibitions. The data were further classified into four quality categories: (1) very good, (2) good, (3) sufficient, and (4) very lacking. The study also demonstrated the relevance of imperative speech acts in the film Today We’ll Talk About That Day for teaching Indonesian to Grade 10 students, particularly in the context of discussion text material at SMA Muhammadiyah 2 Palembang.